Nunca Más, Nie Wieder: ethical aspects of remembering in the narratives of Ravensbrück. Survivors, their descendants and other persons engaged in memory work - Kadlecova, Sarka (Hispania Nova, 2019)
This article deals with collective memory of a women’s concentration camp in Nazi Germany. The objective of this text is to examine the possibility of the construction of a shared memory by survivors of the concentration camp Ravensbrück, their descendants and other persons, mainly women, engaged in the memory work around this particular site of memory. Drawing on Jeffrey Alexander’s social theory of trauma, a number of examples of the intensive cultural and political work necessary for creating a shared trauma will be presented. Based on the data created during multi-sited ethnographic fieldwork, the article will explore ethical aspects of the process of remembering and the fabrication of collective trauma.